Systemic indices of skeletal muscle damage and recovery of muscle function after exercise: effect of combined carbohydrate-protein ingestion - Betts, J. A.; Toone, R. J.; Stokes, K. A.; Thompson, D. (Applied Physiology, Nutrition, and Metabolism, 2009)
Previous studies indicate that exercise-induced muscle damage may be attenuated when protein is included in a carbohydrate recovery supplement. This study was designed to examine systemic indices of muscle damage, inflammation, and recovery of muscle function, following strenuous exercise, with ingestion of either carbohydrate alone or a carbohydrate-protein mixture. Seventeen highly trained volunteers participated in 2 trials in a randomized order, separated by approximately 9 weeks. Each trial involved 90 min of intermittent shuttle-running, either with ingestion of a 9% sucrose solution during and for 4 h after (1.2 g/kg body mass/h) or with the same solution plus 3% whey protein isolate (0.4 g/kg body mass/h). Blood was sampled throughout and 24 h after each trial to determinate the systemic indices of muscle damage and inflammation. An isokinetic dynamometer was used to establish reliable baseline measurements of peak isometric torque for knee and hip flexors and extensors, which were then followed-up at 4-, 24-, 48-, and 168-h postexercise. The exercise protocol resulted in significantly elevated variables indicative of muscle damage and inflammation, while peak isometric torque was immediately reduced by 10%-20% relative to baseline, across all muscle groups tested. However, none of these responses varied in magnitude or time-course between the treatments, or between participants` first and second trials. The addition of whey protein isolate to a dietary carbohydrate supplement ingested during and for 4 h following strenuous exercise did not attenuate systemic indices of muscle damage or inflammation, nor did it restore muscle function more rapidly than when the carbohydrate fraction was ingested alone.